127k views
2 votes
M<1 =

m<2 =
m<3=
m<4=

Blank # 1
Blank #2
Blank #3
Blank #4

M<1 = m<2 = m<3= m<4= Blank # 1 Blank #2 Blank #3 Blank #4-example-1

1 Answer

4 votes

Answer:

m < 1 = 23°

m < 2 = 90°

m < 3 = 67°

m < 4 = 113°

Explanation:

m < 2 is a right angle. Therefore, m < 2 = 90°.

Since m < 2 is 90°, then m < 1 + m < 67° = 90°

To solve for m < 1: subtract m < 67° from m < 2:

90° - m < 67° = 23°. Thereforem m < 1 = 23° (acute angle).

m < 67° + m < 4 = 180° (supplementary angles).

To solve for m < 4: subtract m < 67° from 180°

180° - m < 67° = 113° .

Therefore, m < 4 = 113° (obtuse angle).

The sum of m < 4 and m < 3 = 180° (supplementary angles).

180° - m < 4 = m < 3

180° - 113° = 67°

Therefore, m < 3 = 67° (acute angle).

User Luke Bajada
by
6.9k points